(untitled) (Precision Medicine Communications, 2022)
Currently, no biomarkers are available for detecting toxicities induced by the vascular endothelial growth factor (VEGF) tyrosine kinase inhibitors (TKI). Quintanilha and colleagues employed a discovery-validation approach to identify the markers of toxicities induced by these agents. A total of 140 cancer patients treated with Sorafenib (TARGET) were genotyped for 56 single nucleotide polymorphisms (SNPs). A separate cohort of 201 sorafenib-treated patients was tested for associations between grade ≥2 toxicities and the most significant SNPs. Specific SNPs displayed an association with composite toxicities, dermatological toxicities, diarrhea, and grade ≥2 hypertension. The association with grade ≥2 toxicities with the validated SNP was further investigated in 82 (Italian cohort) and 107 (LCCC 1029) patients administered regorafenib. Logistic regressions were employed to elucidate SNP-toxicity associations, followed by a meta-analysis of the conducted research for inverse variance. The results demonstrated that the presence of SNPs in KDR increased the risk of grade ≥2 composite toxicities in TARGET patients. In the Italian cohort, toxicities were associated with the variant rs4864950. Thus, their studies identified a predictor of VEGF TKI-induced toxicities. The Pharmacogenomics Journal (2022) DOI: 10.1038/s41397-022-00279-3.